Diasporic Cross-Currents in Michael Ondaatje’s Anil’s Ghost and Anita Rau Badami’s The Hero’s Walk - Härting, Heike (Studies in Canadian Literature / Études en littérature canadienne, 2003)
Both Anil's Ghost and The Hero's Walk advance conceptual cross-fertilizations between Canadian literature and diaspora studies and intervene into current discourses of diaspora. While Michael Ondaatje's novel envisions diaspora in largely ahistorical terms as a condition of Anil's nomadic identity, cultural relativism, and political failure, Anita Rau Badami's novel fashions patterns of diasporic identification — rather than identity — around moments of stillness and disruption that generate new forms of communal and individual autonomy. From different perspectives, then, both novels illuminate the theoretical fallacies that consist in turning the concept of diaspora into another all-encompassing allegory of postcolonial subjectivity.